2020
DOI: 10.1177/0363546520910428
|View full text |Cite
|
Sign up to set email alerts
|

Individuals With an Anterior Cruciate Ligament–Reconstructed Knee Display Atypical Whole Body Movement Strategies but Normal Knee Robustness During Side-Hop Landings: A Finite Helical Axis Analysis

Abstract: Background: Atypical knee joint biomechanics after anterior cruciate ligament reconstruction (ACLR) are common. It is, however, unclear whether knee robustness (ability to tolerate perturbation and maintain joint configuration) and whole body movement strategies are compromised after ACLR. Purpose: To investigate landing control after ACLR with regard to dynamic knee robustness and whole body movement strategies during sports-mimicking side hops, and to evaluate functional performance of hop tests and knee str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…5 A]). Moderate-certainty evidence with small effect from 13 studies (933 participants) [ 34 , 104 , 106 , 108 110 , 112 114 , 117 119 , 122 ] showed greater peak/RoM trunk flexion in individuals with ACLR compared to controls during landing tasks (SMD = 0.48; 95% CI = 0.21–0.75; Z = 3.48, P = 0.005 [Fig. 5 A]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 A]). Moderate-certainty evidence with small effect from 13 studies (933 participants) [ 34 , 104 , 106 , 108 110 , 112 114 , 117 119 , 122 ] showed greater peak/RoM trunk flexion in individuals with ACLR compared to controls during landing tasks (SMD = 0.48; 95% CI = 0.21–0.75; Z = 3.48, P = 0.005 [Fig. 5 A]).…”
Section: Resultsmentioning
confidence: 99%
“…5 C]). Moderate-certainty evidence from 6 studies (568 participants) [ 34 , 104 , 106 , 113 , 116 , 119 ] showed no differences between groups for ipsilateral trunk lean (peak/RoM) during landing tasks (SMD = 0.23; 95% CI = − 0.05 to 0.51; Z = 1.58, P = 0.11 [Fig. 5 C]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 15-segment 6 degrees of freedom model was constructed in Visual3D (Version 5.02.30; C-Motion) from 56 passive spherical markers attached with double-coated adhesive tape on the skin at anatomic landmarks, as previously described in detail. 33 Participants wore rigid clusters with 4 markers on each thigh to improve construct validity by reducing the effects of soft tissue artifacts. 12 The marker data were tracked with Qualisys Track Manager software (Version 2.11) and filtered at 15 Hz with a critically dampened digital filter before being used to calculate the outcome variables.…”
Section: Methodsmentioning
confidence: 99%
“…The ACL-reconstructed legs in HIGH-FEAR and LOW-FEAR were compared to the nondominant legs among CTRL (non-preferred leg when kicking a ball) for all between-group analyses, in accordance with previous biomechanical studies from our research group. [39][40][41][42] Mean values were calculated and used for each outcome variable from the 5 successful trials.…”
Section: [H2]statistical Analysismentioning
confidence: 99%